Folded strains of a bistable composite tape-spring. (15th December 2021) - Wang, Bing; Seffen, Keith A.; Guest, Simon D.
Abstract: The bistable composite tape-spring (CTS) structure has received increasing interest in industrial applications, especially in aerospace engineering. Its ability to fold under large displacements makes it attractive as a hinge-safety assembly, with reduced weight, complexity and maintenance compared to the conventional lock-link connections. The shape of a CTS during folding has been studied; but research on its folded strain levels is limited. We devise a novel method to evaluate the strain evolution in a folded CTS. This is achieved by embedding strain gauges in a CTS sample before ''rolling'' the fold through them at constant fold angle: the rolling shape thus provides an exact profile of the strain along the CTS centreline. The strain has maximum levels at the centre of the folded CTS, as expected, whilst a new shoulder-like local peak feature is observed. A finite element (FE) analysis is performed to reveal expected levels of strain: the experimental strain profile is then compared to reveal fundamental correlations. Further insight therefore can be drawn from the FE model, which is beneficial in maintaining structural integrity, and ensure the composite is not over-confined and liable to damage during and after folding.